Penerapan Model Pembelajaran MEA dalam Meningkatkan Kemampuan Pemecahan Masalah Ekonomi dan Bisnis Siswa Kelas XI MPLB : Implementation of the MEA Learning Model in Improving the Economic and Business Problem-Solving Skills of Class XI MPLB Students - Bunga Gesty; Efni Cerya (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The ability of 11th-grade students of MPLB SMK Negeri 1 Padang Panjang in dealing with economics-business problems is still low, as evidenced by only 11.5% being able to achieve completion in the 2023/2024 MID Exam. This condition prompted an experimental study aimed at assessing the effectiveness of the Means-Ends Analysis (MEA) learning model compared to conventional methods commonly used. This study used a Nonequivalent Control Group Design with a total of 68 students, divided into two classes: an experimental class that received MEA-based learning and a control class that continued to use traditional methods. Research data were collected through initial tests (pre-test) and final tests (post-test), then analysed using a paired sample t-test assisted by SPSS. The results showed a significant increase in the experimental class with an average post-test score reaching 71.65 (an increase of 22.5 points), while the control class only increased slightly to 50.88. The significance value of 0.000 < 0.05 strengthens the evidence that MEA is more effective than conventional methods. Thus, the implementation of the MEA model has been proven not only to improve learning outcomes but also to foster students' problem-solving skills, critical thinking, and creativity. Theoretically, this research enriches the literature on the application of MEA to vocational learning; practically, it provides an alternative, innovative strategy for vocational high school teachers; and politically, it aligns with the spirit of the Independent Curriculum, which emphasises active, collaborative, and student-centred learning.